2017
DOI: 10.1177/0194599817692529
|View full text |Cite
|
Sign up to set email alerts
|

Online Tonsillectomy Resources: Are Parents Getting Consistent and Readable Recommendations?

Abstract: Objective Parents frequently refer to information on the Internet to confirm or broaden their understanding of surgical procedures and to research postoperative care practices. Our study evaluated the readability, comprehensiveness, and consistency around online recommendations directed at parents of children undergoing tonsillectomy. Study Design A cross-sectional study design was employed. Setting Thirty English-language Internet websites. Subjects and Methods Three validated measures of readability were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…In an effort to include websites that were found using all three search terms, we only evaluated 10 sites. Although a previous study by Eysenbach and Köhler showed that consumers routinely only review a small number of the many websites listed in search results, limiting our study to 10 sites led to low statistical power. The Google search algorithm alters search results based on the type of device used to perform the search, personal search history, geographic location, and browser type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to include websites that were found using all three search terms, we only evaluated 10 sites. Although a previous study by Eysenbach and Köhler showed that consumers routinely only review a small number of the many websites listed in search results, limiting our study to 10 sites led to low statistical power. The Google search algorithm alters search results based on the type of device used to perform the search, personal search history, geographic location, and browser type.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies in the otolaryngology literature evaluating online resources that have found wide heterogeneity in information regarding surgical procedures, including tonsillectomy, Zenker's diverticulum, and thyroidectomy . We seek to evaluate the online resources and educational materials available for the most commonly performed otolaryngologic surgery in children: TT placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise applications in otorhinolaryngology are not yet reported. [212] FRES: Flesch Reading Ease Score; a: tonsillectomy AND parent; tonsillectomy AND children; tonsillectomy AND care; tonsillectomy AND "caring for your child"; tonsils AND surgery AND care; tonsillectomy AND "what to do"; tonsillectomy AND "parent education"; child AND tonsils AND removed; hospital AND tonsillectomy AND information; tonsil AND information AND surgery AND pediatric.…”
Section: Social Mediamentioning
confidence: 99%
“…Furthermore, a multicenter randomized controlled trial, the Childhood Adenotonsillectomy Study, showed that sizable minority of children with obstructive sleep apnea have resolution of symptoms over time without surgery 7 . As such, the decision for surgery may be complex and multifaceted for the parent 8 , and they may seek information from external (e.g., online) sources to enhance their surgical decisions and knowledge 9 .…”
Section: Introductionmentioning
confidence: 99%